ANALYSIS OF USER REQUIREMENTS FOR SPORT SCHOOL SYSTEM - Ceriņa, Sandra; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Author analyzes user requirements of “Rezekne Chidren and Youth Sport School” and their coherence with the school management system “E-klase”. Author completed system analysis, statistical survey and system comparison to develop recommendations how to improve sociotechnical system of school.